Metal organic frameworks for hydrogen purification. (1st July 2021) - Mao, Donglai; Griffin, John M.; Dawson, Richard; Fairhurst, Alasdair; Bimbo, Nuno
Abstract: High purity hydrogen is one of the key factors in determining the lifetime of proton exchange membrane (PEM) fuel cells. However, the current industrial processes for producing high purity hydrogen are not only expensive, but also come with low energy efficiencies and productivity. Finding more cost-effective methods of purifying hydrogen is essential for ensuring wider scale deployment of PEM fuel cells. Among various hydrogen purification methods, adsorption in porous materials and membrane technologies are seen as two of the most promising candidates for the current industrial hydrogen purification methods, with metal organic frameworks (MOF) being particularly popular in research over the last decade. Despite many available reviews on MOFs, most focus on synthesis and production, with few reports focused on performance for hydrogen purification. This review describes the working principle and performance parameters of adsorptive separations and membrane materials and identifies MOFs that have been reported for hydrogen purification. The MOFs are summarised and their performance in separating hydrogen from common impurities (CO2, N2, CH4, CO) is compared systematically. The challenges of commercial application of MOFs for hydrogen purification are discussed. Highlights: MOFs that have been reported for H2 purification are summarised and compared. MOFs with the highest H2 permeance value are identified. MOFs with the highest H2 separation factors against impurity gases are identified. MOFs with a good balance of permeance and selectivity have been identified. Future research direction of metal-organic frameworks for H2 purification is discussed.